Nurses' Psychosocial Barriers to Suicide Risk Management - Sharon Valente (Nursing Research and Practice)
Suicide remains a serious health care problem and a sentinel event tracked by The Joint Commission. Nurses are pivotal in evaluating risk and preventing suicide. Analysis of nurses' barriers to risk management may lead to interventions to improve management of suicidal patients. These data emerged from a random survey of 454 oncology nurses' attitudes, knowledge of suicide, and justifications for euthanasia. Instruments included a vignette of a suicidal patient and a suicide attitude questionnaire. Results. Psychological factors (emotions, unresolved grief, communication, and negative judgments about suicide) complicate the nurse's assessment and treatment of suicidal patients. Some nurses (𝑛=122) indicated that euthanasia was never justified and 11 were unsure of justifications and evaluated each case on its merits. Justifications for euthanasia included poor symptom control, poor quality of life, incurable illness or permanent disability, terminal illness, and terminal illness with inadequate symptom control or impending death, patient autonomy, and clinical organ death. The nurses indicated some confusion and misconceptions about definitions and examples of euthanasia, assisted suicide, and double effect. Strategies for interdisciplinary clinical intervention are suggested to identify and resolve these psychosocial barriers.